Contribution to the Issue of Determining Nationality and Citizenship on the Basis of Racial Criteria in the Protectorate of Bohemia and Moravia (Theatrum historiae, 2025)
This paper focuses on the Nazi conception of citizenship in the Protectorate of Bohemia and Moravia, revealing the contradictions between ideology and the practical possibilities of nationality policy. The Nazis aimed to capture not only the indigenous German minority but also the so-called “national middle layer” in linguistically mixed areas. It often happened that opportunists or collaborators sought German citizenship, while people of German or mixed origin had reservations about joining the Volksgemeinschaft. The study analyses the chaos associated with granting German citizenship until 1941, when it was decided to subject applicants to racial assessment according to SS criteria. Granting German citizenship became a tool of the Germanisation policy, with racial criteria also being applied to mixed marriages. The research reveals the pseudoscientific nature of Nazi racial policy. The study brings new insights into the practical application of Nazi racial policy in the context of the occupation of the Czech lands and performs a critical evaluation of its impact on the fates of specific individuals.
Keywords: German (Reich) Citizenship; Racism; Nazi Racial Policy; Protectorate of Bohemia and Moravia; Racial Selection; SS Race and Settlement Main Office; Mixed Marriages; Germanisation